Does Organizational Support Moderate the Influence of Family–Work Conflict on Career Progression?. Issue 2 (June 2023) - Adu, Isaac Nyarko; Twumasi, Evelyn; Boakye, Kwame Owusu; Kyei-Frimpong, Michael
One of the major challenges faced by female employees is the difficulty in juggling between family and work roles. This affects their career progression in the organization. Therefore, this study aims at examining the buffering role of perceived organizational support in the relationship between family–work conflict and career progression. The study utilizes the quantitative research paradigm and employed the survey research design. Responses from two hundred and twenty (220) female officers of the Ghana Revenue Authority–Customs Division were analysed using Smart PLS – 3.0 and Haye's (2017) PROCESS macro. The result of the study revealed that family–work conflict is negatively related with career progression (career goal progression, professional ability development, and promotion speed). Perceived organizational support moderated the association between family–work conflict and both professional ability development and promotion speed. However, it did not moderate the relationship between family–work conflict and career goal progression. These findings imply that for female officers to progress in the midst of family–work conflict, organizations must institute support systems and policies to reduce its impact on career progression.